PENGARUH PENDIDIKAN KESEHATAN DENGAN MEDIA LEMBAR BALIK TENTANG PENCEGAHAN STUNTING PADA CALON PENGANTIN - Naila Fauziatin; Apoina Kartini; S. A. Nugraheni (Dian Nuswantoro Semarang, 2019)
Naila Fauziatin1, Apoina Kartini2, S.A Nugraheni31Magister Promosi Kesehatan, Fakultas Kesehatan Masyarakat, Universitas Diponegoro2,3Fakultas Kesehatan Masyarakat, Universitas DiponegoroEmail : nailafauzia729@gmail.comÂ ABTRACTEfforts to assess stunting must be done on the right candidate for the bride who will prepare for the pregnancy. Knowledge of the status of prospective mothers, the fetus to be conceived, and the quality of the baby to be improved, therefore the knowledge and attitude of the brides. can be enlarged stunting that continues to pass.The research is experimental quasy with a control group non-randomized design. The research subjects were the brides in 4 KUA in Grobogan District, 72 respondents in the intervention group and 72 respondents in the control group. This research will analyzes the differences in knowledge and attitudes of brides before and after the intervention with the media flipchart about stunting prevention. The instrument research uses a structured questionnaire. Data were analyzed by univariate and bivariate using the Wilcoxon test.Statistical test results is p=0,000 which means an increase in the knowledge and attitude of the brides. In this study, reversing media has been proven to increase the knowledge and attitudes of brides in preventing stunting. It is expected that the KUA and the health office will increase health promotion efforts in stunting prevention to brides.Keywords: Flipchart, Stunting, Bride